EVALUASI PELAYANAN PUBLIK PRODUK HUKUMONLINE.COM UNTUK MENGETAHUI KEBUTUHAN PELANGGAN KASUS PT JUSTIKA SIAR PUBLIKA - Ahmad H Sutawidjaya; Pista Suci Asmarani (Universitas Mercu Buana, 2018)
Hukumonline.com is a legal information provider company in Indonesia that is committed to providing up-to-date legal information for all levels of society. The phenomenon of the problems in this study, from the products owned by Hukumonline.com, there are some products that are less satisfactory for customers. Broadly speaking, there are two things that cause this. First, because the products offered are still incomplete and not in accordance with customer needs. The second is due to the emergence of competitors who market similar products based on online bases. This research was conducted at PT Justika Siar Publika (Hukumonline.com), using 85 samples. The research method uses the concept of Quality Function Development using the Customer Voice (VoC) approach to Quality Houses (HoQ). From the results of the analysis, there are 8 important points that need to be corrected, namely: (1) The search process is facilitated, (2) the regional regulations are equipped, (3) the previous rules are completed, (4) Translate OLD multiplied, (5) The historical features of the regulations are complemented, (6) ILB is sent in accordance with the customer's company background, (7) Retail subscription packages are provided, and (8) Discount prices are provided. So far, there are only 5 points for which the data is improved, namely in points 1 through 5. While 3 points at 6 to 8, it cannot be fixed due to inadequate treatment.